Design and Validation of a Questionnaire for University Students’ Generic Competencies (COMGAU) - Regueiro, Bibiana; Rodríguez-Fernández, José Eugenio; Crespo, Julia; Pino-Juste, Margarita Rosa (Frontiers in Education, 2021)
University, as a social institution as defined in the EHEA, must be a benchmark in the preparation for beginning employment and education for the exercise of active citizenship. Therefore its functions include the development of knowledge and skills needed for appropriate personal performance in various social and professional arenas. This education is complex and requires bringing together specific and generic (or transversal) competencies. The fundamental aim of this study is to present the construction and validation of a questionnaire for evaluating generic competencies acquired via practical service-learning education and the potential employability of university students. Empirical analysis of the reliability and validity of the instrument was performed with a sample of 564 university students (67.2% women), aged between 18 and 59 years old, although with the majority between 18 and 22 (M = 20.96). Following exploratory and confirmatory factor analysis, as well as analysis of the items and the internal consistency of the scale, the results allow us to conclude that the internal consistency and validity of the COMGAU questionnaire are satisfactory. The proposed measurement model incorporates various prior theoretical contributions, and offers a complementary scale that may contribute to advancing research into service-learning and employability.